Single‐fraction image‐guided robotic radiosurgery efficiently controls local prostate cancer recurrence after radical prostatectomy. Issue 4 (5th August 2020) - Spek, A.; Graser, A.; Habl, G.; Muacevic, A.; Fuerweger, C.; Seitz, M.; Haidenberger, A.
Abstract: Purpose: To assess the therapeutic potential of single‐fraction robotic stereotactic ablative body radiotherapy (SABR) in patients with locally recurrent prostate cancer (PC) after radical prostatectomy (RP). Materials and methods: We included 35 patients with biochemical failure after RP with single‐site local recurrence in the prostate bed diagnosed by PSMA PET/CT. About 20/35 pts had previously received post‐surgical adjuvant radiation therapy. High‐resolution multiparametric magnetic resonance imaging (mpMRI) for exact visualization of tumor tissue was performed at 1.5 (n = 23; Siemens Magnetom Aera) or 3 Tesla (n = 12; Siemens Magnetom VIDA, Siemens Healthineers, Erlangen, Germany). Using the MRI and PET/CT dataset for planning, SABR was carried out after ultrasound‐guided placement of a single gold fiducial marker at the site of tumor recurrence using a CyberKnife M6 unit (Accuray Inc., Sunnyvale, USA). Due to the high diagnostic accuracy of PSMA PET/CT and mpMRI, pre‐SABR biopsy of tumor tissue was not deemed necessary. PSMA PET/CT performed in median 88 days before SABR confirmed the absence of distant metastases. MpMRI was performed at a median of 22 days prior to the intervention. SABR was performed in a single fraction with a dose of 20 (5/35), 21 (27/35) or 22 (3/35) Gy. Follow‐up serum PSA was measured every 3 months thereafter. Results: Median patient age was 72 years (57‐80 years) and median time from RP to SABR was 96.8 months (IQR, 69.3‐160.2). Median serum PSA before SABR was 1.38 ng/mL (IQR 0.75‐2.72). At 3 months, median PSA had dropped significantly in 27/35 patients to a median of 0.35 ng/mL (IQR 0.25‐0.68). At 6 months, 30/35 patients showed biochemical response to SABR, while five patients were progressing: three had systemic disease on PSMA PET/CT, while two patients had rising PSA values without a visible correlate on PET/CT. The median follow‐up time was 16 months. Grade 1 genitourinary (GU) toxicity was reported in 3/35 patients (9%) and grade 1 gastrointestinal (GI) toxicity in 2/35 patients (6%), respectively. Conclusion: SABR is an efficient new treatment option in the management of single‐site local recurrent PC without the evidence of systemic disease; due to its very low toxicity, it is an alternative to surgical re‐treatment or other focal therapies. It can significantly delay the onset of androgen deprivation therapy (ADT) in biochemical failure after radical prostatectomy.